Prevalence of PsychoSocial Problems and their Risk Factors among School-Going Middle Adolescents: An Exploratory Study - Basheerahamed J. Sikandar; K. Kavitha (Indian Journal of Psychiatric Nursing)
Background: Adolescents are at risk of various psychosocial problems, due to pressure from parents, educational agencies, peers, and society. Often, it is not recognized and goes unnoticed. There is an immense need to screen this group for early detection and proper management. Aim: The aim of this study was to assess the prevalence of psychosocial problems among adolescents and to determine their risk factors. Methodology: The study employed a nonexperimental, exploratory, cross-sectional research design with a quantitative approach. Using a two-stage random sampling technique, a total of 2030 adolescents from 37 schools were chosen. The data collection tool for study participants consisted of three parts: (a) A sociodemographic proforma, (b) a pediatric symptom checklist-youth report, and (c) a checklist for assessing determinants of psychosocial problems. Results: Three hundred five (15.02%) of the 2030 respondents had significant impairment to internalizing problems, 350 (17.24%) to attention deficit problems, and 378 (18.62%) to externalizing problems. Pediatric symptom checklist scores and academic performance showed a moderately positive correlation. There is a significant association between psychosocial problems and adolescent characteristics at a P = 0.05 level of significance. Conclusion: Adolescents have a high prevalence of psychosocial problems such as anxiety and attention deficit. Periodic screening, counseling, and referral to psychotherapy can help to lessen the severity of the condition and improve psychosocial well-being.